TRANSFORMATION OF LEADERSHIP MANAGEMENT BY BUILDING A CULTURE OF LITERACY IN INCREASING THE INTEREST OF READING IN STUDENTS - Nisak, Hairun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Leadership transformation is needed in an institution to change patterns and develop existing interests and talents in institutions to improve quality. Building a literacy culture is intended to grow and strengthen interest in reading in students. This study aims to analyze and understand the transformation of a leader in increasing students' interest in reading by implementing a literacy culture in an institution, namely SDN Kotaanyar III, Kotaanyar Village, Kotaanyar District, Probolinggo Regency. This study uses a qualitative approach to the type of case study. The survey results show that management leadership in building a literacy culture is implemented using; Compulsory reading habits (PWB), Strengthening HR, and Integrity of Infrastructure. With the management transformation carried out by leaders in building cultural literacy, they can make it happen by fostering children's reading interest, writing skills, language proficiency and information processing skills